P185 Evaluation of the LENT Prognostic Score in a Large Tertiary Pleural Service. (12th November 2015) - Balata, H; Anwar, N; Foden, P; Al-Aloul, M; Holme, J; Evison, M
Abstract : Introduction and objectives: Reliable predictors of survival in malignant pleural effusions (MPE) have far reaching applications in clinical practice, not least tailoring individual treatment strategies. The 'LENT' score (pleural fluid L actate dehydrogenase; E astern Cooperative Oncology Group performance score; N eutrophil-to-lymphocyte ratio; T umour type) was developed and validated as a clinical prognostic scoring system from three international prospective patient databases. 1 The aim of this study was to evaluate the LENT score in a further UK population of patients with MPE, geographically separate from those in the original study. Methods: Our hospital is a large tertiary centre for a physician-led pleural service (including medical thoracoscopy), a regional mesothelioma centre and a regional thoracic surgical centre. A retrospective study of all patients with positive (i.e. diagnostic for malignancy) pleural cytology or histology from 2010 to 2014 was undertaken. This timeframe allowed a minimum of 12 months follow-up for all patients. Survival data was obtained from national death registries. All patients in whom all LENT criteria were available were included in the analysis. A Kaplan-Meier curve and a Cox regression model were used to assess the LENT risk category. Harrell's C statistic was used to assess the accuracy of the regression model and mortality rates at time points of interest were calculated. Results: The LENT score was calculated for 101 patients diagnosed with MPE. The median survival (days, IQR) for the low (n = 18), medium (n = 54) and high risk (n = 29) groups were: 254 (152–602), 102 (40–301) and 16 (7–42). In the high risk group, only 31% of patients survived 1 month and 7% survived 6 months. There is a statistically significant difference in the survival times in the different risk groups according to the log-rank test (p < 0.001). Harrell's C statistic in this cohort is 0.69 (see Figure 1 ). Conclusions: The LENT scoring system has again been shown to be a good tool for predicting survival in patients with MPE when applied to a geographically distinct cohort of patients to the original study. The LENT score continues to be a clinically valuable tool in the assessment of patients with MPE. Reference: 1 Clive AO, et al . Thorax 2014;69 (12):1098–104